Dolomite for supplementation of desalinated drinking water in Saudi Arabia with magnesium, calcium, and hydrogen carbonate ions - Ali A. Al Hamzah; Abdulrahman S. Alofi; Abdulrahman A. Abid; Jamal M. Salama; Ahmed A. Al Kubaish; Christopher M. Fellows (Discover Water)
Abstract Magnesium (Mg) in drinking water is important for cardiovascular health and it is anticipated that the World Health Organization will introduce minimum Mg recommendations. The Kingdom of Saudi Arabia is dependent on desalinated water which has a low Mg content and it is necessary to find a cost-effective means of supplementation. Dolomite (CaMg(CO3)2) is available at a similar cost to the limestone currently used in post-treatment. Replacement of limestone with dolomite in existing contactors in two commercial desalination plants was effective in raising magnesium concentrations in the produced water by 2.4 ± 0.5 ppm (Shoiabah, Multi-Stage Flash desalination) and 2.9 ± 0.2 ppm (Al Khobar, Reverse Osmosis desalination), sufficient to lift total Mg above the Saudi Arabian guideline value of 5 ppm.